15-Deoxy-△12,14-Prostaglandin J2 Promotes Resolution of Experimentally Induced Colitis - Kim, Wonki; Jang, Jeong-Hoon; Zhong, Xiancai; Seo, Hyungseok; Surh, Young-Joon (Frontiers in Immunology, 2021)
Uncontrolled macrophage activation causes failure to resolve gut inflammation and has been implicated in the pathogenesis of inflammatory bowel diseases (IBD). 15-Deoxy-△12,14-prostaglandin J2 (15d-PGJ2), one of endogenous lipid mediators formed from arachidonic acid during the inflammatory process, has been reported to terminate inflammation. However, the pro-resolving effect of 15d-PGJ2 on intestinal inflammation and underlying molecular mechanisms remain largely unknown. In the present study, we examined the effects of 15d-PGJ2 on the resolution of dextran sulfate sodium (DSS)-induced murine colitis that mimics human IBD. Pharmacologic inhibition of prostaglandin D synthase (PGDS) responsible for the synthesis of 15d-PGJ2 hampered resolution of inflammation in the colonic mucosa of mice treated with DSS. Notably, intraperitoneal injection of 15d-PGJ2 accelerated the resolution of experimentally induced colitis. 15d-PGJ2 treatment reduced the number of neutrophils and M1 macrophages, while it increased the proportion of M2 macrophages. Moreover, 15d-PGJ2 treated mice exhibited the significantly reduced proportion of macrophages expressing IL-6 with concomitant suppression of STAT3 phosphorylation in the colonic mucosa of DSS-treated mice. Taken together, these findings clearly indicate that 15d-PGJ2, endogenously generated from arachidonic acid by cyclooxygenase-2 and PGDS activities in inflamed tissue, promotes resolution of intestinal colitis.